Case Study: Providing Tens and Retrowalking on Knee Osteoarthritis Functional Activities - Segita, Riri; Munawarah, Siti (PT. Riset Press International, 2024)
Osteoarthritis is a degenerative joint disease associated with cartilage damage in the joints, involving a complex interactive process of joint degradation, consisting of repair processes in the cartilage, bone, and synovium followed by secondary components of inflammation. This disease is commonly found in patients over the age of 50. This study aims to investigate the effects of TENS (Transcutaneous Electrical Nerve Stimulation) and Retrowalking on functional activity in osteoarthritis knee in the year 2023. The research design employed is a quasi-experimental one-group pretest-posttest design. The population in this study was 232 individuals, with a sample size of 10 respondents. Sampling technique was done through purposive sampling. Bivariate analysis results indicate the impact of TENS and Retrowalking on functional activity in osteoarthritis knee, with an average increase in functional activity of 23.270 and a significance level (α) of 0.005. It can be concluded that TENS and Retrowalking have been shown to affect the increase in functional activity in osteoarthritis knee. Therefore, it is hoped that hospitals can implement TENS and Retrowalking interventions for osteoarthritis knee patients.